IMPROVING STUDENTS’ SPEAKING SKILLS THROUGH STORYTELLING METHOD AT ISLAMIC JUNIOR HIGH SCHOOL DARUL MU’MININ - Indah Meydi Sari (Universitas Panca Sakti Bekasi, 2022)
This study aims to determine how far the students' ability to speak English has progressed and experimented with using the storytelling method to learn English. This study employs the classroom action research method. The objects of the research were 32 students from the VIII.1 class at Islamic Junior High School Darul Mu'minin. There were three meetings where this research was done. Each session lasts for two hours or 70 minutes. At each meeting, the researcher wrote down everything that happened. Then, the researcher used statistical analysis to determine how much the students' speaking skills improved and how many got passing grades. Before the storytelling method was used to improve students' speaking skills, the percentage obtained was less than 75%. However, students' speaking abilities improved by more than 75% after using the storytelling method. It means that the storytelling method has been proven effective in improving students' speaking skills. The students' speaking abilities improved in all areas, including comprehension, fluency, vocabulary, grammar, and pronunciation.This is evidenced by the holding of three meetings conducted by the researchers that yielded good results